Improved Topology For Line-Commutated Converter Hvdc With Four-Pole System - Mohammed, Sabah Ramadhan (2019)
The ground/sea electrode or metallic return is an essential part of the existing high-voltage direct current (HVDC) power transmission systems for carrying its return current. Besides the costly presence of the ground/sea electrode or metallic return in the conventional HVDC topologies, the ground/sea electrode is producing severe adverse effects on the environment and alternating current (AC) power systems nearby (e.g. corrosion of buried metallic structures, soil/water overheating, DC bias in power transformers, etc.). This thesis proposes a novel four-pole system (4PS) for line-commutated converter (LCC) HVDC transmission. This system aims to eliminate ground/sea electrode or metallic return and increase the reliability and density of power transmission. The operating principles of the proposed system are presented, followed by detailed mathematical analysis of the conventional bi-pole system (2PS) and the proposed 4PS. Mathematical results show that the electrical power can be transferred through four effective parallel DC circuits with the 12-pulse operation in the 4PS instead of only two DC circuits with the 12-pulse operation as in the existing 2PS. Furthermore, under the same power capacity transmitted in both systems 2PS and 4PS, the results show an increase in system reliability and power transmission density of the 4PS approximately 2 and √2 times, respectively, in comparison with the 2PS. In addition, the Total Harmonic Distortion (THD) simulation results of the AC currents improved in a novel 4PS by 2.12 % at AC system 1 and 0.89 % at AC system 2 in comparison with the conventional 2PS. The proposed system performance has been verified by simulation and experimental results. Simulation and experimental results showed that the proposed 4PS topology can eliminate ground electrode or metallic return, produce four effective parallel DC circuits with 12-pulse operation and increase the reliability and power density.